Proposição de metodologia de reconciliação de lavra para fábricas de cimento Portland - Pedro Hespanha Almeida (2022)
Mined ores are the main raw material on the mining value chain and are studied and modelled through geological survey data. The uncertainties regarding ore tonnage and grade on short-term operation remain, no matter how good the geological models are. Deviations on production process can propagate with harmful consequences to subsequent activities on the value chain, reaching the final product, while harming the economic and socio-environmental performance of the mining companies. Performing the mine reconciliation is a way to use the data generated along the value chain to check the model and improve it. Mine reconciliation is a geometallurgical method of gathering data of production along the mining and plant process and comparing it at different points, to check the model, and can also be used to proactively detect problems like mining dilution or bad sampling practices. Although it is more common in metal mining, it is being shown that applications of mine reconciliation on industrial minerals sector are possible. This study intends to analyze the mining value chain of Portland cement: limestone and clay mining and its processing into clinker. The similarities and differences between this specific sector and metal mining are discussed, and an adapted methodology to reconcile mining operations on the cement industry is proposed. Afterwards, two case studies are carried out in operating cement plants, to test the proposed methodology and to evaluate the future potential of its practice, as well as the benefits generated and its scope of application. To have increasingly better predictive models, it is important to integrate the primary activities of the mining value chain. Even though geological uncertainties cannot be eliminated, the mine reconciliation is indeed an important step towards this end.